FORMULASI PENAMBAHAN AMPAS TAHU TERHADAP KANDUNGAN KIMIA DAN AKSEPTABILITAS PRODUK OTAK-OTAK IKAN TENGGIRI - Dewi Sartika; Asriyanti Syarif (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
Tofu waste is a side product that obtained from the manufacturing of tofu. Substitute soy pulp out on making local dish called